Economic development of the U.S.S.R. - Modak, A.G. (Bombay, 1982)
The book begins with a brief account of Soviet economic history. The chapter concerned first of all analysis the consequences of the passing of the Act of Emancipation in 1861. In fact, the Czarist policies in the years preceding the October Revolution widened the gap between the rich classes and the poor masses. Ultimately the Bolsheviks succeeded in leading these masses. They were, therefore, expected to launch a new course of development. They accordingly launched various five-year plans. The first chapter accordingly provides readers with a brief assessment of the ten Five-Year Plans of the Soviet economy. The next two chapters throw light on the events which took place in the Soviet Union just before the beginning of the planned development of the USSR. The following couple of chapters deals with the formulation and implementation of plans. The awareness on our part that agriculture is the most vulnerable sector of the Soviet economy leads us to devote two special chapters for analysing respectively the nature of Soviet farming and the agricultural policies of the Soviet Government. With this background, the remarkable development of the industrial economy of the Soviet Union has been reviewed in the next chapter. The same chapter briefly explains the problems encountered in the industrial development of the USSR during the midfifties.
Keywords: Economic development